RELATIONSHIPS BETWEEN CHARACTERISTICS OF LOCAL GOVERNMENT AND WEBSITE BASED FINANCIAL TRANSPARENCY - Widyastuti, Gabriela Amanda; damayanti, dena natalia; marwata, marwata (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 2, Agustus 2021 (pp.243-431)DO - 10.24843/JEKT.2021.v14.i02.p08, 2021)
It is important to manifest financial transparency of local government as a means of monitoring the misuse of public resources and preventing cases of corruption. One of the local governments that succeeded in achieving the best transparency in Indonesia is Central Java. Based on 2019 Central Java Local Government financial data, this research is aimed to find evidence whether there are relationships between the characteristics of local government and financial transparency of local government. The evidence is obtained through the results of statistical analysis, namely multiple linear regression analysis. The results of this research show that the size of local government, the tenure of regional heads, the structure of regional revenues, and regional financial independence have a positive relationship to the financial transparency of local government.